Conveyance of residuals from water and wastewater treatment (American Society of Civil Engineers, 2000)
Annotation A manual for design and practicing engineers involved in devices that transport residuals from water and wastewater treatment, focusing on recognizing changes in concentrations, composition, rheology, and transport characteristics at various points in sludge processing and how these changes affect transport of residuals. Introduces sludge/slurry/solids classification and methodology, then explains rheology and distribution of water in sludge, discusses how physical and chemical attributes of solids affect moisture levels, and overviews residuals conveyance devices. Details transport of thickened, dewatered, granular, and compactable residuals. Includes four case histories. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Sewage sludge -- Management.; Sewage sludge -- Characterization.; Sewage disposal plants -- Design and construction.; Water treatment plant residuals -- Management.; elektronické knihy; electronic books